World history - Ancient civilizations through the Renaissance - Burstein, Stanley Mayer; Shek, Richard Hon-Chun (Holt McDougal, Houghton Mifflin Harcourt, 2014)
Unit 1. Early humans and societies. Chapter 1. Uncovering the past -- Chapter 2. The Stone Ages and early cultures -- Unit 2. Mesopotamia, Egypt and Kush. Chapter 3. Mesopotamia and the Fertile Crescent -- Chapter 4. Ancient Egypt and Kush -- Unit 3. Civilization in India and China. Chapter 5. Ancient India -- Chapter 6. Ancient China -- Unit 4. Foundations of Western ideas. Chapter 7. The Hebrews and Judaism -- Chapter 8. Ancient Greece -- Chapter 9. The Greek world -- Unit 5. The Roman world. Chapter 10. The Roman Republic -- Chapter 11. Rome and Christianity -- Unit 6. Islamic and African civilizations. Chapter 12. The Islamic world -- Chapter 13. Early African civilizations -- Unit 7. Empires of Asia and the Americas. Chapter 14. China -- Chapter 15. Japan -- Chapter 16. The Early Americas -- Unit 8. Renewal in Europe. Chapter 17. The Early Middle Ages -- Chapter 18. The Later Middle Ages -- Chapter 19. The Renaissance and Reformation -- Chapter 20. Science and exploration.